Mild preflowering drought priming improves stress defences, assimilation and sink strength in rice under severe terminal drought - Bahuguna, R.N.; Tamilselvan, A.; Muthurajan, R.; Solis, C.A.; Jagadish, S.V.K. (Commonwealth Scientific and Industrial Research Organisation, 2018)
Drought stress is a prominent and persisting constraint for sustaining global rice (Oryza sativa L.) production. Priming with mild drought can be effective in reducing the impact of severe terminal drought stress affecting seed set and grain filling in rice. The cultivars N22 (drought tolerant), NSIC Rc222 and IR64 (high yielding, drought sensitive) were tested for short-term mild drought priming before flowering and subsequently exposed to severe drought stress either at the highly sensitive flowering or at the early grain filling stage under greenhouse conditions. Drought stress increased oxidative damage and reduced photosynthesis and sink enzymatic activity, ultimately reducing seed set (20–46%) and grain yield (22–68%) across cultivars. However, priming with mild drought significantly reduced oxidative damage, and increased photosynthesis, stomatal conductance and enzymatic activity, contributing to improved sink strength, thereby significantly reducing seed set (7–18%) and grain yield (12–59%) losses. The higher activity of key enzymes associated with sink strength such as cell wall invertase and sucrose synthase in primed plants probably reduced drought-induced losses at the grain filling stage. The findings support mild drought priming before flowering as a promising strategy for reducing yield penalty by providing partial protection against subsequent severe terminal drought stress. However, application of mild drought priming at the field level would need further investigation.